La psicomotricidad en el desarrollo integral de niños y niñas de la Unidad Educativa Liceo Policial Riobamba - Hernández Lluay, Yajaira Fernanda (2024)
The objective of this research work was to analyze psychomotor skills in the comprehensive development of boys and girls of the Liceo Policial Riobamba Educational Unit. The study was conducted with eighteen students from Initial II "B" and twenty from First Grade "A". To evaluate the psychomotor variable, the Psychomotor Development Test (TEPSI) was used, which measured fine and gross motor skills, as well as coordination, language, and balance. The purpose of this research was to identify psychomotor skills and comprehensive development, providing a thorough understanding of child growth and proposing educational strategies that promote the complete development of students. Regarding the integral development variable, an observation sheet was used that covers the emotional, social, and cognitive aspects of the children. The research was guided by a quantitative approach, bibliographic information from various research works, and scientific journals, and the contribution of researchers was analyzed. The results of the TEPSI test for Initial II “B” indicate that (90%) of them are in a normal range, (10%) are in the risk range, with no students identified in the delay range, the First year of Basic “A” students are within a normal range, without any student at risk or with delay in psychomotor development. In the observation sheet in general, students show positive development in the areas evaluated, most students demonstrate adequate or outstanding skills in fine motor, cognitive, language, social, emotional, and self-care development. Keywords: Psychomotor skills, comprehensive development, early childhood education, motor skills.